Angular analysis of the decay B+→K+μ+μ− in proton-proton collisions at √s=8 TeV; Physical Review D; Vol. 98, iss. 11 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Baydali S. A. Sergey Anatolievich (2018, 2018)
Title screen